Mediastinal Hematoma as a Potential Complication of Endovascular Intracranial Intervention - Salvador F. Gutierrez‐Aguirre; Otavio F. De Toledo; Eduarda M. Freitas; Victor H.C. Benalia; Amin Aghaebrahim; Ricardo A. Hanel; Eric Sauvageau (Stroke: Vascular and Interventional Neurology)
Objective To highlight the rare incidence of mediastinal hematoma as a complication associated with transradial access, as reported in both cardiovascular and neurovascular fields. Interventionists must be aware of this potential risk and the strategies to manage it. Case Presentation A 66‐year‐old woman presented to an outside hospital's emergency department with 2 months of dizziness and vertigo. A right posterior communication artery aneurysm was discovered incidentally on workup images. On discussing potential options, including observation, the patient opted for endovascular intervention. The aneurysm was treated using a Woven Endobridge Single‐Layer Sphere (SLS) intrasaccular flow disrupter device. After the procedure, the patient was extubated but subsequently required reintubation because of the context of stridor. Radiologic evaluation revealed a mediastinal hematoma, which was suspected to be a direct complication from the transradial access. This required immediate treatment with coil embolization of the perforated vessel at the subclavian artery originating from the costocervical trunk. Conclusion Mediastinal hematoma is a rare complication after neurointerventional procedures by transradial access. Prompt diagnosis and appropriate treatment are critical to managing this potentially lethal condition.